Detergent-compatible fungal cellulases - Niyonzima, Francois N (Folia microbiologica, 2021)
Detergent enzymes are currently added to all powder and liquid detergents that are manufactured. Cellulases, lipases, amylases, and proteases are used in the detergency to replace toxic phosphates and silicates and to reduce high energy consumption. This makes the use of enzymes in detergent formulation cost effective. Fungi are producers of important extracellular enzymes for industrial use. The fungal and bacterial cellulases maintain the shape and color of the washed garments. There is a high demand for cellulases at the market by detergent industries. With this high demand, genetic engineering has been a solution due to its high production of detergent-compatible cellulases. Fungi are the famous source for detergent-compatible cellulases production, but still, there is a lack of the cost-effective process of alkaline fungal cellulase production. Review papers on detergent-compatible bacterial cellulase and amylase and detergent-compatible fungal and bacterial proteases and lipases are available, but there is no review on detergent fungal cellulases. This review aims to highlight the production, properties, stability, and compatibility of fungal cellulases. It will help other academic and industrial researchers to study, produce, and commercialize the fungal cellulases with good aspects.
Keywords: celulasy; Fungi; Cellulases; genetické inženýrství; stabilita enzymů; Fungal Proteins; houby; Enzyme Stability; Detergents; fungální proteiny; Genetic Engineering; detergenty